Nonaqueous electrolyte solution, electrochemical device, and electronic device
By using a nonaqueous electrolyte containing the compound of formula I in lithium-ion batteries, the problems of poor discharge performance and short cycle life of lithium-ion batteries under high temperature conditions are solved, and longer cycle life and better high temperature performance are achieved.
Patent Information
- Application Number
- CN202412000110.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing lithium-ion batteries have poor discharge performance under high temperature conditions and have a short cycle life, making it difficult to meet the demands of electronic products at unconventional temperatures.
A nonaqueous electrolyte is used, which contains specific compounds of formula I. Through the electronegative properties of these compounds, coordinate with the metal elements on the electrode surface, form a protective layer, and combine with the dissolved metal cations to avoid their deposition at the negative electrode, thereby extending the cycle life of the battery and improving high temperature performance.
It significantly extends the cycle life of the electrochemical device, improves the discharge performance at high temperatures, and ensures the stability and efficiency of lithium-ion batteries under various temperature conditions.
Smart Images

Figure CN119786719A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a non-aqueous electrolyte, an electrochemical device and an electronic device. Background Art
[0002] As people's demand for electronic products such as mobile phones, laptops, cameras, etc. increases year by year, lithium-ion batteries play an increasingly important role in our daily lives as the power source of electronic products. Diversified operating conditions also put forward new requirements for the performance of lithium-ion batteries at unconventional temperatures. As one of the important components of lithium-ion batteries, the physical and chemical properties of the electrolyte are directly related to the discharge performance of the battery. Therefore, it is imperative to develop an electrolyte with better discharge performance, especially better high-temperature performance. Summary of the invention
[0003] The embodiments of the present application provide a non-aqueous electrolyte, an electrochemical device, and an electronic device, which can achieve better discharge performance, especially better high-temperature performance.
[0004] In a first aspect, the present invention provides a non-aqueous electrolyte solution, including a compound of formula I:
[0005]
[0006] Among them, M + Selected from lithium ion, sodium ion, potassium ion, silver ion, cesium ion, ammonium cation, piperidinium cation, pyrrolidinium cation or imidazolium ion; based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula I is a%, and 0.01≤a≤1.
[0007] Based on the non-aqueous electrolyte of the embodiment of the present application, the cyano group contained in the compound of formula I included therein has a strong electronegativity. On the one hand, it can form a coordination with the metal element on the surface of the positive electrode and adsorb on the surface of the electrode to form an electrode protective layer; on the other hand, the anion of the compound of formula I can combine with the metal cation dissolved on the electrode to avoid the deposition of metal ions on the negative electrode, inhibit the increase of the internal resistance of the battery, thereby extending the cycle life of the electrochemical device and improving the high temperature performance.
[0008] In some embodiments, 0.01≤a≤0.5. Based on the above embodiments, the present application further controls the mass content of the compound of formula I in the non-aqueous electrolyte within the above range, thereby further avoiding the deposition of metal ions at the negative electrode, inhibiting the increase in the internal resistance of the battery, thereby extending the cycle life of the electrochemical device and improving the high temperature performance.
[0009] In some embodiments, the ammonium cation is represented by Formula II, the piperidinium cation is represented by Formula III, the pyrrolidinium cation is represented by Formula IV, and the imidazolium ion is represented by Formula V:
[0010]
[0011] Among them, R 11 , R 12 , R 13 , R 14 , R 21 , R 22 , R 31 , R 32 , R 41 and R 42 Each is independently selected from C1 to C4 alkyl, C2 to C4 alkenyl or C3 to C4 alkynyl. Based on the above embodiments, the compound of formula I in the non-aqueous electrolyte includes a cation of the above structure, which can further avoid the deposition of metal ions at the negative electrode, inhibit the increase of the internal resistance of the battery, thereby extending the cycle life of the electrochemical device and improving the high temperature performance.
[0012] In some embodiments, the compound of Formula I includes at least one of the following compounds:
[0013]
[0014]
[0015] Based on the above embodiments, the present application can further avoid the deposition of metal ions at the negative electrode and inhibit the increase of the internal resistance of the battery by selecting the above-mentioned compound of formula I, thereby extending the cycle life of the electrochemical device and improving the high-temperature cycle performance.
[0016] In some embodiments, the non-aqueous electrolyte includes vinylene carbonate; based on the total mass of the non-aqueous electrolyte, the mass proportion of vinylene carbonate is b%, 0.01≤b≤3. Based on the above embodiments, the non-aqueous electrolyte of the present application further includes vinylene carbonate, which has a unique unsaturated cyclic structure and a high reduction potential, and can be reduced and polymerized in advance to form a stable protective film, thereby synergistically extending the cycle life of the electrochemical device with the compound of formula I and improving the high temperature cycle performance.
[0017] In some embodiments, the non-aqueous electrolyte includes fluoroethylene carbonate; based on the total mass of the non-aqueous electrolyte, the mass proportion of fluoroethylene carbonate is c%, 0.1≤c≤10. Based on the above embodiments, the non-aqueous electrolyte of the present application further includes fluoroethylene carbonate, which has a higher reduction potential and can be preferentially reduced to form a film on the surface of the negative electrode, while forming an inorganic-organic composite protective film containing LiF and a polymer, thereby synergistically extending the cycle life of the electrochemical device with the compound of formula I and improving the high temperature cycle performance.
[0018] In some embodiments, the non-aqueous electrolyte includes at least one of a compound of Formula VI or a compound of Formula VII:
[0019]
[0020] Where R 51 , R 52 , R 61 and R 62 Each is independently selected from an unsubstituted or fluorine-substituted C1 to C2 alkyl group; based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula VI is d%, 20≤d≤60; and / or, based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula VII is e%, 20≤e≤60. Based on the above embodiments, the non-aqueous electrolyte of the present application further includes a compound of formula VI or a compound of formula VII, which can effectively increase the wettability of the electrode and ensure the transmission of ions in the gaps of the electrode; on the other hand, both the compound of formula VI and the compound of formula VII have a relatively low viscosity, which can significantly reduce the transmission resistance of ions in the electrolyte. By controlling their content within a reasonable range, they can work together with the compound of formula I to improve the high-temperature cycle performance while taking into account the improvement of the low-temperature performance.
[0021] In some embodiments, R 51 , R 52 , R 61 , R 62 Each is independently selected from an unsubstituted or fluorine-substituted C1 to C2 alkyl group. Based on the above embodiments, the present application can further extend the cycle life of the electrochemical device by selecting a compound of formula VI or formula VII containing the above groups, while improving the high temperature cycle performance and the low temperature performance.
[0022] In some embodiments, the compound of Formula VI includes at least one of the following compounds:
[0023] Based on the above embodiments, the present application can further extend the cycle life of the electrochemical device by selecting the above compound of formula VI, while improving the high-temperature cycle performance and the low-temperature performance.
[0024] In some embodiments, the compound of Formula VII includes at least one of the following compounds:
[0025] Based on the above embodiments, the present application can further extend the cycle life of the electrochemical device by selecting the above-mentioned compound of formula VII, while improving the high-temperature cycle performance while also improving the low-temperature performance.
[0026] In some embodiments, the non-aqueous electrolyte comprises a compound of Formula VIII:
[0027]
[0028] Among them, R 71 , R 72 , R 73 and R 74 Each is independently selected from C1 to C4 alkyl, C1 to C4 alkoxy, C2 to C4 alkenyl, C2 to C4 alkynyl, phenyl or acryloyloxy, and at least one is selected from C2 to C4 alkenyl, C2 to C4 alkynyl or acryloyloxy; based on the total mass of the non-aqueous electrolyte, the mass proportion of VIII compound is f%, 0.01≤f≤1. Based on the above embodiment, the non-aqueous electrolyte of the present application further includes a compound of formula III, and the unique alkenyl, alkynyl and other groups in the compound of formula III can be oxidatively polymerized to form a cross-linked structure, which can form a stable and dense protective layer at the electrode interface, inhibit the occurrence of side reactions, and reduce the loss of active lithium, so that it can cooperate with the compound of formula I to further extend the cycle life of the electrochemical device, while improving the high-temperature cycle performance and the low-temperature performance.
[0029] In some embodiments, the compound of Formula VIII includes at least one of the following compounds:
[0030]
[0031] Based on the above embodiments, the present application can further extend the cycle life of the electrochemical device by selecting the above compound of formula VIII, while improving the high-temperature cycle performance and the low-temperature performance.
[0032] In a second aspect, an embodiment of the present application provides an electrochemical device, including a positive electrode plate and the above-mentioned non-aqueous electrolyte; the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode material layer includes at least one of a nickel-cobalt-manganese ternary material, lithium manganate, lithium nickel manganate, or a lithium-rich manganese-based material. In some embodiments, the nickel-cobalt-manganese ternary material includes LiNiCoMnO2, and the lithium nickel manganate includes LiNi 0.5 Mn 1.5O4. The lithium-rich manganese-based material includes xLi2MnO3·(1-x)LiMO2, where 0 < x < 1. Based on the above embodiments, the positive electrode material layer of the electrochemical device of the present application includes a manganese-containing positive electrode active material, and the manganese ions contained therein are more likely to dissolve and then deposit on the negative electrode. On this basis, by using the above non-aqueous electrolyte in combination, the compound of Formula I in the electrolyte can combine with the manganese ions dissolved in the electrode during the cycle, avoiding the deposition of manganese ions on the negative electrode, better inhibiting the increase in the internal resistance of the battery, and thus more significantly extending the cycle life of the electrochemical device and improving the high-temperature performance.
[0033] In a third aspect, an embodiment of the present application provides an electronic device, which includes the above electrochemical device. Detailed implementation manners
[0034] In order to make the objectives, technical solutions and advantages of the present application clearer, the following further describes the present application in detail with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0035] In a first aspect of an embodiment of the present application, an electrochemical device is provided, which includes a non-aqueous electrolyte, a positive electrode, a negative electrode and a separator.
[0036] Non-aqueous electrolyte
[0037] The non-aqueous electrolyte used in the electrochemical device of the present application includes a lithium salt and a non-aqueous solvent that dissolves the lithium salt.
[0038] The non-aqueous electrolyte includes a compound of Formula I:
[0039]
[0040] Wherein, M + is selected from a lithium ion, a sodium ion, a potassium ion, a silver ion, a cesium ion, an ammonium cation, a piperidinium cation, a pyrrolidinium cation or an imidazolium ion. Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound of Formula I is a%, where 0.01 ≤ a ≤ 1. Preferably, 0.01 ≤ a ≤ 0.5. For example, the value of the mass percentage of the compound of Formula I in the non-aqueous electrolyte can be 0.01, 0.05, 0.1, 0.5, 0.7, 0.9, 1 or a value within the range composed of any two of these values. The non-aqueous electrolyte includes a compound of Formula I, which can combine with the metal cations dissolved in the electrode during the cycle, avoiding the deposition of metal ions on the negative electrode, inhibiting the increase in the internal resistance of the battery, and thus extending the cycle life of the electrochemical device and improving the high-temperature performance.
[0041] In some of the embodiments, the ammonium cation is as shown in Formula II, the piperidinium cation is as shown in Formula III, the pyrrolidinium cation is as shown in Formula IV, and the imidazolium ion is as shown in Formula V:
[0042]
[0043] Among them, R 11 , R 12 , R 13 , R 14 , R 21 , R 22 , R 31 , R 32 , R 41 and R 42 Each is independently selected from C1 to C4 alkyl, C2 to C4 alkenyl or C3 to C4 alkynyl. The compound of formula I in the non-aqueous electrolyte includes a cation of the above structure, which can further avoid the deposition of metal ions at the negative electrode, inhibit the increase of the internal resistance of the battery, thereby extending the cycle life of the electrochemical device and improving the high temperature performance.
[0044] In some embodiments, the compound of formula I comprises at least one of the following compounds:
[0045] The non-aqueous electrolyte includes the compound of formula I, which can further avoid the deposition of metal ions on the negative electrode, inhibit the increase of the internal resistance of the battery, thereby extending the cycle life of the electrochemical device and improving the high-temperature cycle performance.
[0046] In some embodiments, the non-aqueous electrolyte includes vinylene carbonate. Based on the total mass of the non-aqueous electrolyte, the mass proportion of vinylene carbonate is b%, 0.01≤b≤3. For example, the mass proportion of vinylene carbonate in the non-aqueous electrolyte can be 0.01, 0.55, 1.14, 1.80, 2.13, 2.57, 3 or a value within the range of any two of these values. The non-aqueous electrolyte further includes vinylene carbonate, which can extend the cycle life of the electrochemical device and improve the high temperature cycle performance.
[0047] In some embodiments, the non-aqueous electrolyte includes fluoroethylene carbonate. Based on the total mass of the non-aqueous electrolyte, the mass proportion of fluoroethylene carbonate is c%, 0.1≤c≤10. For example, the mass proportion of fluoroethylene carbonate in the non-aqueous electrolyte can be 0.1, 0.7, 3.0, 5.8, 6.9, 9.6, 10 or a value within the range of any two of these values. The non-aqueous electrolyte further includes fluoroethylene carbonate, which can extend the cycle life of the electrochemical device and improve the high temperature cycle performance.
[0048] In some embodiments, the non-aqueous electrolyte comprises at least one of the compound of formula VI or the compound of formula VII:
[0049]
[0050] Where R 51 , R 52 , R 61 , R 62 Each is independently selected from an unsubstituted or fluorine-substituted C1 to C2 alkyl group. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula VI is d%, 20≤d≤60. For example, the mass proportion of the compound of formula VI in the non-aqueous electrolyte can be 20, 26, 39, 47, 55, 60 or a value in the range composed of any two of these values. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula VII is e%, 20≤e≤60. For example, the mass proportion of the compound of formula VII in the non-aqueous electrolyte can be 20, 21, 31, 44, 60 or a value in the range composed of any two of these values. The non-aqueous electrolyte further includes the above-mentioned compound of formula VI or compound of formula VII, which can extend the cycle life of the electrochemical device, while improving the high-temperature cycle performance and improving the low-temperature performance.
[0051] In some embodiments, R 51 , R 52 , R 61 , R 62 Each is independently selected from unsubstituted or fluorine-substituted C1 to C2 alkyl groups. The compound of formula VI or formula VII containing the above groups in the non-aqueous electrolyte can further extend the cycle life of the electrochemical device, improving the high temperature cycle performance while also improving the low temperature performance.
[0052] In some embodiments, the compound of formula VI comprises at least one of the following compounds:
[0053] Selecting the compound of formula VI in the non-aqueous electrolyte can further extend the cycle life of the electrochemical device, improving the high-temperature cycle performance while also improving the low-temperature performance.
[0054] In some embodiments, the compound of formula VII includes at least one of the following compounds:
[0055] Selecting the compound of formula VII in the non-aqueous electrolyte can further extend the cycle life of the electrochemical device, improving the high-temperature cycle performance while also improving the low-temperature performance.
[0056] In some embodiments, the non-aqueous electrolyte comprises a compound of formula VIII:
[0057]
[0058] Among them, R 71 , R 72 , R 73 and R 74 Each is independently selected from an alkyl group of C1 to C4, an alkoxy group of C1 to C4, an alkenyl group of C2 to C4, an alkynyl group of C2 to C4, a phenyl group or an acryloxy group, and at least one is selected from an alkenyl group of C2 to C4, an alkynyl group of C2 to C4 or an acryloxy group. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the VIII compound is f%, and 0.01≤f≤1. For example, the mass proportion of the VIII compound in the non-aqueous electrolyte can be 0.01, 0.10, 0.31, 0.48, 0.79, 0.85, 0.91, 1.00 or a value within the range of any two of these values. The non-aqueous electrolyte further includes the above-mentioned compound of formula VIII, which can extend the cycle life of the electrochemical device, while improving the high temperature cycle performance and improving the low temperature performance.
[0059] In some embodiments, the compound of formula VIII includes at least one of the following compounds:
[0060] Further selecting the compound of formula VIII in the non-aqueous electrolyte can further extend the cycle life of the electrochemical device, improving the high-temperature cycle performance while also improving the low-temperature performance.
[0061] The present application has no particular restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonyl imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalate borate) (LiBOB) or lithium difluorooxalate borate (LiDFOB). Based on the mass of the electrolyte, the mass proportion of the lithium salt may be 8% to 10%, for example, the mass proportion of the lithium salt may be 8%, 9%, 10% or a range consisting of any two of these values.
[0062] The non-aqueous electrolyte of the present application may further include other organic solvents, for example, it may include but is not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. For example, it may include but is not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0063] Positive electrode
[0064] The positive electrode includes a positive electrode current collector and a positive electrode material layer provided on at least one surface of the positive electrode current collector.
[0065] In some embodiments, the positive electrode material layer includes at least one of nickel-cobalt-manganese ternary material, lithium manganate, lithium nickel manganate or lithium-rich manganese-based material. In some embodiments, the nickel-cobalt-manganese ternary material includes LiNiCoMnO2, and the lithium nickel manganate includes LiNi 0.5 Mn 1.5 O4, and the lithium-rich manganese-based material includes xLi2MnO3·(1-x)LiMO2, where 0 < x < 1. For example, the lithium-rich manganese-based material includes 0.5Li2MnO3·0.5LiMO2. The positive electrode material layer includes a manganese-containing positive electrode active material. By using the above non-aqueous electrolyte system in combination, the increase in the internal resistance of the battery can be better inhibited, thereby more significantly extending the cycle life of the electrochemical device and improving the high-temperature performance.
[0066] In some embodiments, the positive electrode material layer includes a positive electrode conductive material. The type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of the positive electrode conductive material may include but are not limited to carbon blacks such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials can be used alone or in any combination.
[0067] In some embodiments, the positive electrode material layer includes a positive electrode binder. The type of the positive electrode binder is not particularly limited, and in the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, etc.; rubber polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, etc.; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers, styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrides; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, propylene-α-olefin copolymers; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.
[0068] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0069] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0070] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0071] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0072] negative electrode
[0073] The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.
[0074] In some embodiments, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO w (0.5<w<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.
[0075] In some of the embodiments, the negative electrode material layer further includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of the negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some of the embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0076] In some embodiments, the negative electrode material layer further includes a conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0077] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode material layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.
[0078] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.
[0079] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.
[0080] Diaphragm
[0081] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode. The diaphragm is used to separate the positive electrode plate and the negative electrode plate to prevent internal short circuit of the electrochemical device, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.
[0082] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.
[0083] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0084] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.
[0085] The present application also provides an electronic device, which includes the electrochemical device of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0086] Example
[0087] Hereinafter, taking lithium-ion batteries as an example, examples and comparative examples are given to more specifically describe the implementation of the electrochemical device of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0088] Example 1-1
[0089] 1. Preparation of positive electrode
[0090] The positive electrode active material LiMn2O4, the conductive agent conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on one surface of the positive electrode current collector aluminum foil and dried to obtain a positive electrode sheet coated with a positive electrode material layer on one side. The above steps are repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After cold pressing, striping, and welding, a positive electrode sheet is obtained.
[0091] 2. Preparation of electrolyte
[0092] In a dry argon atmosphere glove box, lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solution of ethylene carbonate, propylene carbonate, and a compound of formula I to obtain a non-aqueous electrolyte. Wherein, based on the total mass of the non-aqueous electrolyte, the mass proportion of LiPF6 was 10.0%, the mass proportion of ethylene carbonate was 20%, the mass proportion of the compound of formula I was as shown in Table 1, and the balance was propylene carbonate.
[0093] 3. Preparation of negative electrode
[0094] Artificial graphite is used as the negative electrode active material. The negative electrode active material, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry. The negative electrode slurry is evenly coated on one surface of the negative electrode current collector copper foil and dried to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. After cold pressing, striping, and welding, a negative electrode sheet is obtained.
[0095] 4. Preparation of diaphragm
[0096] A porous polyethylene film with a thickness of 15 μm was used as the separator.
[0097] 5. Preparation of lithium-ion batteries
[0098] The positive electrode sheet, negative electrode sheet and separator are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in a packaging bag, and after dehydration at 80°C, the above electrolyte is injected and packaged. After the process of formation hot pressing, degassing, trimming, capacity testing, etc., a lithium-ion battery is obtained.
[0099] 6. Test methods
[0100] (1) High temperature cycle performance test
[0101] Take the lithium-ion battery prepared in the above steps, place it in a 45°C constant temperature test box, and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.2V at a constant current of 0.5C, then charge it to a current of 0.025C at a constant voltage of 4.2V, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.5C, and record it as the initial discharge capacity C0. Cycle this step 300 times, record the discharge capacity C1 after 300 cycles, and calculate the high-temperature cycle capacity retention rate of the lithium-ion battery.
[0102] High temperature cycle capacity retention rate % = C1 / C0×100%.
[0103] (2) Low temperature discharge performance test
[0104] Take the lithium-ion battery prepared in the above steps, place it in a high and low temperature box, adjust the temperature to 25°C, and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. The lithium-ion battery that has reached a constant temperature is discharged to 3.0V at a current constant current of 0.5C, then charged to 4.2V at a current constant current of 0.5C, and then charged to a current of 0.025C at the 4.2V voltage constant voltage. Also at a temperature of 25°C, discharge to 3.0V at a current constant current of 0.5C, and record the discharge capacity as the initial discharge capacity. At a temperature of 25°C, charge to 4.2V at a constant current of 0.5C, and then charge to a current of 0.025C at the 4.2V voltage constant voltage. Afterwards, place the lithium-ion battery at a temperature of 0°C and let it stand for 30 minutes to keep the temperature of the lithium-ion battery consistent with the outside temperature. At 0°C, discharge to 3.0V at a current constant current of 0.5C, and record the discharge capacity as the low-temperature discharge capacity.
[0105] Low-temperature discharge capacity retention rate %=(low-temperature discharge capacity / initial discharge capacity)×100%.
[0106] The lithium ion batteries of the following embodiments or comparative examples differ from those of embodiment 1-1 only in that the type and mass proportion of the compound of formula I, the mass proportion of vinylene carbonate, the mass proportion of fluoroethylene carbonate, and the type of positive electrode active material are adjusted according to Table 1. The performance test results of the lithium ion batteries of the embodiments and comparative examples are shown in Table 1 below.
[0107] Table 1
[0108]
[0109] *In the above table, the mixing ratio of the two compounds of formula I in Examples 1-4, 1-18 and 1-19 is 1:1 by mass.
[0110] It can be seen from Table 1 that the lithium ion battery prepared in the embodiment of the present application has a better high temperature cycle capacity retention rate when the non-aqueous electrolyte includes the compound of formula I and its mass ratio satisfies 0.01≤a≤1.
[0111] In particular, the lithium-ion battery prepared in the embodiment of the present application, when the mass proportion of the compound of formula I in the non-aqueous electrolyte further satisfies 0.01≤a≤0.5, the lithium-ion battery has a better high-temperature cycle capacity retention rate. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the non-aqueous electrolyte further includes vinylene carbonate, and its mass proportion satisfies 0.01≤b≤3, the lithium-ion battery has a better high-temperature cycle capacity retention rate. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the non-aqueous electrolyte further includes fluoroethylene carbonate, and its mass proportion satisfies 0.1≤c≤10, the lithium-ion battery has a better high-temperature cycle capacity retention rate.
[0112] The lithium ion batteries of the following Examples 2-1 to 2-23 differ from those of Example 1-17 only in that the type and mass ratio of the compound of Formula VI, the type and mass ratio of the compound of Formula VII, and the type and mass ratio of the compound of Formula VIII are adjusted according to Table 2.
[0113] Table 2
[0114]
[0115] *In the above table, the mixing ratio of the two compounds in Example 2-22 and Example 2-23 is 1:1 by mass.
[0116] As can be seen from Table 2, the lithium-ion battery prepared in the embodiment of the present application has a better high-temperature cycle capacity retention rate and low-temperature discharge capacity retention rate when the non-aqueous electrolyte further includes a compound of formula VI or a compound of formula VI, and the mass proportions thereof satisfy 20≤d≤60 or 20≤e≤60, respectively. When the non-aqueous electrolyte further includes a compound of VIII, and the mass proportion thereof satisfies 0.01≤f≤1, the lithium-ion battery has a better high-temperature cycle capacity retention rate and low-temperature discharge capacity retention rate.
[0117] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A non-aqueous electrolyte, characterized in that: Includes compounds of formula I: Among them, M + is selected from lithium ion, sodium ion, potassium ion, silver ion, cesium ion, ammonium cation, piperidinium cation, pyrrolidinium cation or imidazolium ion; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula I is a%, and 0.01≤a≤1.
2. The non-aqueous electrolyte according to claim 1, characterized in that 0.01≤a≤0.5。 3. The non-aqueous electrolyte according to claim 1, characterized in that The ammonium cation is shown in Formula II, the piperidinium cation is shown in Formula III, the pyrrolidine cation is shown in Formula IV, and the imidazolium ion is shown in Formula V: Among them, R 11 , R 12 , R 13 , R 14 , R 21 , R 22 , R 31 , R 32 , R 41 and R 42 Each is independently selected from a C1 to C4 alkyl group, a C2 to C4 alkenyl group or a C3 to C4 alkynyl group.
4. The non-aqueous electrolyte according to claim 3, characterized in that The compound of formula I includes at least one of the following compounds:
5. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The non-aqueous electrolyte includes vinylene carbonate; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the vinylene carbonate is b%, and 0.01≤b≤3.
6. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The non-aqueous electrolyte includes fluoroethylene carbonate; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the fluoroethylene carbonate is c%, and 0.1≤c≤10.
7. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The non-aqueous electrolyte comprises at least one of a compound of formula VI or a compound of formula VII: Where R 51 , R 52 , R 61 and R 62 Each is independently selected from unsubstituted or fluorine-substituted C1 to C4 alkyl; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula VI is d%, 20≤d≤60; And / or, based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula VII is e%, 20≤e≤60.
8. The non-aqueous electrolyte according to claim 7, characterized in that The R 51 , R 52 , R 61 and R 62 Each is independently selected from unsubstituted or fluorine-substituted C1 to C2 alkyl groups.
9. The non-aqueous electrolyte according to claim 8, characterized in that The compound of formula VI comprises at least one of the following compounds:
10. The non-aqueous electrolyte according to claim 8, characterized in that The compound of formula VII includes at least one of the following compounds:
11. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The non-aqueous electrolyte comprises a compound of formula VIII: Among them, R 71 , R 72 , R 73 and R 74 Each is independently selected from C1 to C4 alkyl, C1 to C4 alkoxy, C2 to C4 alkenyl, C2 to C4 alkynyl, phenyl or acryloyloxy, and at least one is selected from C2 to C4 alkenyl, C2 to C4 alkynyl or acryloyloxy; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the VIII compound is f%, and 0.01≤f≤1.
12. The non-aqueous electrolyte according to claim 11, characterized in that The compound of formula VIII includes at least one of the following compounds:
13. An electrochemical device, characterized in that: Comprising a positive electrode sheet and the non-aqueous electrolyte according to any one of claims 1 to 12; The positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes at least one of a nickel-cobalt-manganese ternary material, lithium manganate, lithium nickel manganate or a lithium-rich manganese-based material.
14. An electronic device, characterized in that: An electrochemical device comprising the electrochemical device of claim 13.
Citation Information
Cited By
Electrolyte for aluminum batteries
RU2861834C1